The Chemical Investigation of the Seed Fat of Diospyros peregrina - Kumar Jain, Rakesh; Garg, S.C. (Asian Journal of Chemistry, 2010)
The fixed oil from the seeds of Diospyros peregrina Gurke has been investigated for its physico-chemical properties and chemical composition. The gas chromatographic analysis has revealed the oil to consist of the glyceride of caprylic acid (0.95%), capric acid (1.26%), myristic acid (0.47%), palmitic acid (31.63%), stearic acid (8.24%), oleic acid (43.10%) and linoleic acid (14.26%). The unsaponifiable matter has been found to be a mixture of ,β-amyrin and ,β-sitosterol.